З ІСТОРІЇ ПРОЕКТІВ УТВОРЕННЯ ПОРТО-ФРАНКО В МІСТАХ ПІВДЕННОЇ УКРАЇНИ ПЕРШОЇ ПОЛОВИНИ ХІХ ст. (Zaporizhzhia Historical Review, 2021)
The projects of Porto Franco in Southern Ukraine towns in the first part of the XIX century, the circumstances and peculiarities of the project origin and their further destiny are considered in the article. The informative potential of the projects and their importance as memorials of public and social-economic thought of Ukraine at the end of the XVIII ñ the first part of the XIX century are emphasized.